"It Depends on What They Experience in Each Health Facility. Some Are Satisfied, Others Are Not." A MixedMethods Exploration of Health Workers' Attitudes Towards Performance-Based Financing in Burkina Faso - Julia Lohmann; Jean-Louis Koulidiati; Serge MA Somda; Manuela De Allegri (Kerman University of Medical Sciences, 2021)
Background Evidence emerging from qualitative studies suggests the existence of substantial variation in how health workers experience performance-based financing (PBF) within the same setting. To date, however, no study has quantified or systematically explored this within-setting heterogeneity. Considering that differences in health workers' affective reactions to PBF likely constitute an important element mediating the effectiveness of PBF in improving health service delivery, systematic and tangible information will be highly valuable to policy-makers and program managers who aim to maximize positive impacts of PBF. Our study aimed at contributing to filling this gap in knowledge by quantifying health workers' knowledge of, satisfaction with, and perceptions of PBF in Burkina Faso, and exploring factors associated with heterogeneity therein.   Methods The study employed a post-intervention cross-sectional explanatory mixed methods study design with a dominant quantitative component - a structured survey to a total of 1314 health workers from 396 intervention health facilities - and a small and focused qualitative component - key informant interviews with 5 program managers - to triangulate and further elucidate the quantitative findings. Quantitative data were analyzed descriptively as well as using 3-level mixed effects models. Qualitative data were analyzed in a largely deductive process along the quantitative variables and results.   Results Health workers were on average moderately satisfied with PBF overall, with a slight tendency towards the positive and large variation between individuals. Two-thirds of health workers did not have adequate basic knowledge of key PBF elements. Perceived fairness of the performance evaluation process, of the bonus distribution process, and satisfaction with the individual financial bonuses varied dramatically between respondents. Factors associated with heterogeneity in knowledge, satisfaction, and fairness perceptions included responsibility at the facility, general work attitudes, management factors, and training in and length of exposure to PBF.   Conclusion Findings imply that investments into staff training on PBF and manager training on organizational change processes might be beneficial to positive staff attitudes towards PBF, which in turn would likely contribute to improving the effectiveness of PBF.